An Investigation of Client Evaluation of Banking Service Quality in Iraq Banking Business - HASHEM, SHAYMAA DHAFER (The journal of contemporary issues in business and government, 2021)
This study is a comprehensive analysis that aims to access and explain the preferences and perceptions of customers of service quality in Iraq banking and then define the aspects of service quality that lead to the perception of customer service quality in Iraq's banking industry. Customers of universal banks in Iraq were the target demographic of the study. In all 100 universal banks customers, the study was chosen. Reliability, responsiveness, and empathy are three most significant in determining the efficiency of universal banks in Iraq, according to the report. Customers have poor expectations of the overall service levels of universal banks. However, consumers' understanding of the physical dimensions of excellence and durability was found to be the perceptions of customers. The results of the study have shown that the empathy factor is the most influent aspect that determines consumers' understanding of overall service quality. Context factors such as gender, age, income level, and academic skills were found to affect consumer understanding and experience of quality of service. Empathy should be put greater importance since it is found to be the most important aspect of the overall perception of service quality by customers of universal banks in Iraq. Policymakers of universal banks can control the context characteristics of consumers when designing policies to increase quality of service. Future analysis is urged to carry out a cross-country comparison and to compare the findings of the current study in other African countries.